Next-Gen Hybrid Materials: Epoxy Matrices Enhanced by Covalently Anchored Alkylsilane-Nanoparticle Complexes - Salas, Alexis; Jaramillo, Andrés Felipe; Palacio, Daniel Andrés; Medina, Carlos; Rojas, David; Ramírez, Jesús; Cabrera, Gustavo; Meléndrez, Manuel Francisco (Current Approaches in Engineering Research and Technology Vol. 3, 2024)
In this work, the surface modification of zinc oxide nanoparticles (ZnO-NPs) with 3-glycidyloxy-propyl-trimethoxysilane (GPTMS) was investigated. The ZnO-NPs were synthesized using the physical method of continuous arc discharge in controlled atmosphere (DARC-AC). The surface modification was carried out using a chemical method with constant agitation for 24 h at room temperature. This surface functionalization of zinc oxide nanoparticles (ZnO-NPs-GPTMS) was experimentally confirmed by infrared spectroscopy (FT-IR), TGA, and XRD, and its morphological characterization was performed with SEM. The increase in mechanical bending properties in the two final hybrid materials compared to the base polymers was verified. An average increase of 67% was achieved with a moderate decrease in ductility. In the case of compressive strength, they showed mixed results, maintaining the properties. With respect to thermal properties, it was observed that inorganic reinforcement conferred resistance to degradation on the base material, giving a greater resistance to high temperatures.